Education On Clean and Healthy Living Behavior in Prevention Of Pediculosis Capitis Disease - Sutrisno, Joko; Febriani, Elok Aqila (Open Access Health Scientific Journal, 2025)
Background: Factors from pediculosis capitis in the cottage environment are usually caused by a lot of teenager students who don't be able to look after themselves alone or a number of bad nature that doesn't reflect clean and healthy life behavior. So on this study conducted action gift education behavior clean and healthy life (PHBS) with counseling method. This study aimed to know the influence of gift education to prevent the disease pediculosis.Method: This study was held at Pondok Al-Huda Village Islamic Boarding School Sragi Subdistrict Songgon Regency Banyuwangi. Study use type study experiment with design quantitative experiment quasi experimental pre and post design, with sample using simple random sampling as many as 51 respondents. Data analysis using Paired Sample T- Test with condition test normality normally distributed (0.05), however if normality data distribution is not fulfilled so will next with Wilcoxon Test..Results: Results from Test Statistics obtained enhanced behavior life clean and healthy 27 respondents (53%) and enhanced behavior prevention disease pediculosis capitis there are 24 respondents (47%). seen that the value of 0.000 which can be interpreted that the score is not enough from 0.05, so that H1 is accepted means there is influence education behavior life clean and healthy in preventing disease pediculosis Capitis at Pondok Boarding school.Conclusion: Education on clean and healthy living behaviours plays a pivotal role in the prevention of pediculosis capitis. By enhancing knowledge and promoting hygiene practices, communities can significantly reduce the prevalence of this common yet often overlooked condition. Future research should focus on longitudinal studies to evaluate the long-term impact of educational interventions on head lice prevention.